An Evaluation of Soft-drink Wastewater Treatment by Anaerobic Digestion Process - G, Redzwan; C.J, Banks (Malaysian Journal of Science, 2007)
Series of batch operations were conducted for testing the suitability of anaerobic process for the treatment of soft-drink wastewater. No buffering control substances and biomass growth enhancer were added during the experiment although the wastewater used lacked those substances. Each batch operation resulted in the normal methane yield which was between 0.28 to 0.34 m³ per kg COD removed. Nevertheless, with the increments of hydraulic loading up to one-third of the working volume, the treatment operation has unable to further remove the carbonaceous components. This failure was also shown by the cessation of CH₄ production. The final organic mass loading per working volume was at 1.33 kg/m³, which was relatively low to cause failure. Further investigation showed that operation failed because of the methanogenesis process has been subjugated. Impediment of methanogenesis was caused by losses of its alkalinity during effluent withdrawal and addition of influent with low pH. VFAs were found to be as high as 1500 mg/L. Lack of nitrogen source was also the cause of the subjugation when reduction of biomass concentration were also had been observed. Treatment of such wastewater with low nitrogeneous substances and low levels of pH and alkalinity requires additional controlling measures to avoid operational failure.